(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
Agitations for increase in minimum wage are workers’ reaction to fast dwindling purchasing power and also a clamour for relatively more equitable distribution of Nigeria’s wealth. Diminishing purchasing power is an indication that the economy is under-performing. A number of things might have gone wrong in the system including implementation of policies that do not properly fit in with Nigeria’s sensitive and complex socioeconomic setting. Objectives of the study include to find out whether increasing Nigeria’s minimum wage would make the required difference in the purchasing power and standard of living of workers and to suggest an alternative approach to improving the living condition of Nigerian workers. It is recommended that while it may not be completely out of place to increase minimum wage, relevant authorities should rethink and overhaul those policies that do not seem to fit in well in the context of Nigeria’s socioeconomic dynamics, and thereby reposition towards a revival of Nigeria’s ailing economy. It also behoves on the current administration and other leaders of Nigeria to come up with ways to reduce the very wide and widening disparity in pay package between the political class and the civil servants.